Effectiveness Of Mirror Therapy On Extremity Motor Function In Post Stroke Patients: Literature Review - Ratri, Tifany Hayuning (Holistic Nursing Plus, 2025)
Background: Stroke occurs when a blood artery is blocked or ruptured, suddenly cutting off the blood supply to the brain, so that brain tissue does not get enough oxygen and nutrients. The purpose of this literature review is to find out how effective mirror therapy works to improve motor function in the upper extremities of stroke patients. The article search method in this journal review uses several data bases and keywords taken from 2019-2023. The article search obtained 5,436 articles. Good articles are reviewed using the PICOT framework, which reduces the risk of bias when data selection is carried out independently by two authors consisting of design, method, intervention and outcome, where the Population is stroke patients, hemorrhagic using Mirror therapy, There is no comparator, Outcome is improved upper extremity function. as many as 7 selected articles used the RCT (Randomized Control Trial) design. The results of Mirror therapy are an effective rehabilitation technique for stroke patients with mild to severe paralysis. Mirror therapy can be an alternative in terms of increasing their mobility by strengthening muscles and helping with daily activities. It is hoped that this literature review discussion can be used for further and detailed research so that it can be used as a reference for establishing interventions in post-stroke patients.